Outcome of Depression and Anxiety After War: A Prospective Epidemiologic Study of Children and Adolescents. Issue 2 (16th April 2014) - Karam, Elie G.; Fayyad, John; Karam, Aimee N.; Melhem, Nadine; Mneimneh, Zeina; Dimassi, Hani; Tabet, Caroline Cordahi
Abstract: Prospective studies of children exposed to war have not investigated disorders other than posttraumatic stress disorder (PTSD) and have methodological limitations. From a stratified random sample of 386 children and adolescents who had been interviewed 3 weeks after war exposure (Phase 1) a random subsample ( N = 143) was interviewed a year later (Phase 2). PTSD, major depressive disorder (MDD), separation anxiety disorder (SAD), overanxious disorder (OAD), and psychosocial stressors were assessed using structured interviews administered to both children and adolescents and their parents. The prevalence of disorders among the 143 at Phase 1 was MDD 25.9%, SAD 16.1%, OAD 28.0%, and PTSD 26.0%, with 44.1% having any disorder. At Phase 2 the prevalence was MDD, 5.6%; SAD, 4.2%; OAD, 0%; and PTSD, 1.4%, with 9.2% having any disorder. Occurrence of disorders at Phase 1 was associated with older age, prewar disorders, financial problems, fear of being beaten, and witnessing any war event ( OR s ranged from 2.5 to 28.6). Persistence of disorders to Phase 2 was associated with prewar disorders ( OR = 6.0) and witnessing any war event ( OR = 14.3). There are implications for detection of at‐risk cases following wars by screening for adolescents exposed to family violence, those with prewar disorders, and those who directly witnessed war events to target them for specific interventions.